The superior interest of the child in the case of children born in Spain of mothers who do not transmit her nationality by applying the Islamic Law. In particular, the reform of Moroccan Law - Zurita Martín, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The inability of a woman to transmit her nationality to her children in some Islamic systems entails the statelessness of the child in the case of an unmarried mother, since children born out of wedlock are deprived of paternal filiation. This circumstance has forced the DGRN to pronounce on the application of Spanish nationality of the children born in Spain of Moroccan unmarried parents, giving rise to a doctrine in this respect that has been endorsed by the modification of Moroccan Nationality Law. The aim of this paper is to reflect, in the light of the principle of constitutional equality, the evolution of Moroccan legislation in this area, taking as reference the resolutions issued by the DGRN, in order to assess them taking into account the best interests of the child.
Keywords: nationality; filiation; Islamic law; Moroccan law; the best interest of the child